Solasodine-3-O-β-d-glucopyranoside is hydrolyzed by a membrane glucosidase into active molecule solasodine against Candida albicans. (November 2017) - Chang, Wenqiang; Li, Ying; Zheng, Sha; Zhang, Ming; Gao, Yanhui; Lou, Hongxiang
Abstract: Antifungal activity of some natural molecules can be abated or blocked by efflux pumps in Candida albicans, which restricts the discovery of potential antifungal agents. Here we found that the steroidal alkaloid solasodine is active against C. albicans efflux pump-deficient strains but inert towards the wild type. However, the glucosylated solasodine-3- O -β-d -glucopyranoside exhibits antifungal activity towards the wild type strain. Further investigation revealed that the entry of solasodine into C. albicans cells is blocked by efflux pumps. Glucosylation provides an alternative access not disturbed by efflux pumps. Once inside cells, the carried glucosylated solasodine is cleaved into the active molecule solasodine by the glucosidase, which is located in cytoplasm membrane and exhibits selective activity against hydrolyzing glucosyl natural products but not against other monosaccharide-substituted products. This glucosidase is not encoded by orf19.4031, considered homologous to steryl-β-glucosidase encoded by the gene EGH1 in Saccharomyces cerevisiae. Our study reveals that glucosylation is an alternative approach for introducing potential antifungal activity into C. albicans cells and overcoming the drug-resistance resulting from hyperactivation of efflux pumps. Highlights: Solasodine is the active antifungal form of solasodine-3- O -β-d -glucopyranoside. The glucosidase in C. albicans selectively recognizes glucosyl moiety. Glucosylation is an alternative way for some agents to gain the antifungal activity. Glucosylation can be used to overcome antifungal resistance caused by efflux pumps.